Molecular design of new P3HT derivatives: Adjusting electronic energy levels for blends with PCBM - Oliveira, Eliezer Fernando [UNESP]; Lavarda, Francisco Carlos [UNESP] (Elsevier B.V., 2014)
An intensive search is underway for new materials to make more efficient organic solar cells through improvements in thin film morphology, transport properties, and adjustments to the energy of frontier electronic levels. The use of chemical modifications capable of modifying the electronic properties of materials already known is an interesting approach, as it can, in principle, provide a more adequate adjustment of the frontier electronic levels while preserving properties such as solubility. Based on this idea, we performed a theoretical study of poly(3-hexylthiophene) (P3HT) and 13 new derivatives obtained by substitution with electron acceptor and donor groups, in order to understand how the energy levels of the frontier orbitals are modified. The results show that it is possible to deduce the modification of the electronic levels in accordance with the substituent's acceptor/donor character. We also evaluated how the substituents influence the open circuit voltage and the exciton binding energy. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Electronic materials; Organic compounds; Polymers; Computer modelling and simulation; Electronic structure